Clonal hematopoiesis impacts frailty in newly diagnosed multiple myeloma patients: a retrospective multicenter analysis - Elisa Gelli; Claudia Martinuzzi; Debora Soncini; Concetta Conticello; Francesco Ladisa; Giulia Giorgetti; Dario Truffelli; Isabella Traverso; Francesco Lai; Fabio Guolo; Maurizio Miglino; Antonia Cagnetta; et al. (Scientific Reports, 2024)
Abstract Somatic mutations of hematopoietic cells in the peripheral blood of normal individuals refer to clonal hematopoiesis of indeterminate potential (CHIP), which is associated with a 0.5–1% risk of progression to hematological malignancies and cardiovascular diseases. CHIP has also been reported in Multiple Myeloma (MM) patients, but its biological relevance remains to be elucidated. In this study, high-depth targeted sequencing of peripheral blood from 76 NDMM patients revealed CHIP in 46% of them, with a variant allele frequency (VAF) ranging from ~ 1 to 34%. The most frequently mutated gene was DNMT3A, followed by TET2. More aggressive disease features were observed among CHIP carriers, who also exhibited higher proportion of high-risk stages (ISS and R-ISS 3) compared to controls. Longitudinal analyses at diagnosis and during follow-up showed a slight increase of VAFs (p = 0.058) for epigenetic (DNMT3A, TET2, and ASXL1) and DNA repair genes (TP53; p = 0.0123). A more stable frequency was observed among other genes, suggesting different temporal dynamics of CH clones. Adverse clinical outcomes, in term of overall and progression-free survivals, were observed in CHIP carriers. These patients also exhibited weakened immune T-cells and enhanced frailty, predicting greater toxicity and consequently shorter event-free survival. Finally, correlation analysis identified platelets count as biomarker for higher VAF among CHIP carriers, regardless of the specific variant. Overall, our study highlights specific biological and clinical features, paving the way for the development of tailored strategies for MM patients carrying CHIP.